Observaciones sobre los gametofitos de Woodwardia martinezii Maxon et Weatherby y W. spinulosa Mart. & Gal. (Blechnaceae) - Perez-García, Blanca; Riba, Ramón (Instituto de Ecología, A.C., 1993)
Additional Information is given in this paper on morphogenetic features of the gametophyte of two fern species of the Blechnaceae. Woodwardia spinulosa, growing from the North of México to Central America (Nicaragua) has dark brown, bilateral and ellipsoidal spores with wavy and folded perispore; the germination pattern is of Vittaría type and the prothallial  development is of Aspidium type. The mature gametophytes  are bisexual, with antheridia and archegonia typical of  leptosporangiate ferns. Juvenile sporophytes with one or two  leaves were observed 11 months after spore germination.  Woodwardia martinezii is only known from a few localities in  the States of Veracruz and Hidalgo, México; the spores and the  germination and prothallial development patterns are similar to  those of W. spinulosa, butthe spores are larger. Spatulate gametophytes with antheridia and without archegonia were  observed, and also vegetativo gametophytes with apogamous sporophytes. The gametophyte development of these two  species is consistent with other blechnaceous ferns previously  studied.